Ansiedade e sintomas depressivos em adultos e idosos submetidos à cirurgia cardíaca - Lisboa, Debora Dagostini Jorge (2016)
Chronic heart diseases are a group of highly prevalent diseases worldwide, especially related to population aging phenomenon observed in recent years. Among the available treatment for these disorders, we find the heart surgery, an invasive procedure of high risk, which involves complex factors such as cardiac manipulation and cardiopulmonary bypass, which in most cases are accompanied by physical and psychological complications. The need for heart surgery is usually accompanied by fragility and fear on the part of patients, so it is common for the onset or exacerbation of symptoms of anxiety and depression in these individuals and can change the quality of life of patients undergoing cardiac surgery. This research aims to evaluate the presence of symptoms suggestive of depression and anxiety in adults and elderly patients in period before and after cardiac surgery. It is an uncontrolled prospective cohort study in two hospitals in the city of Passo Fundo / RS. Data collection occurred in three different times, preoperative, postoperative during hospitalization and after three months of surgery, through the Questionnaire Clinical Socio-demographic, Rating Scale Anxiety and Depression Level and Quality Questionnaire SF-36 life. It was performed descritova and inferential analysis. The significance level is 0.05. Findings from this study were that patients undergoing cardiac surgery in the evaluated institutions, have the follow up socio-demographic characteristics prevalent: average age of 59.9 years, 44 males (62.9%), white 60 (85, 7), married 47 (67.1%), Catholic 57 (81.4), professional farmer 33 (47.1%), retired 48 (68.6%). Coming from cities in the interior of Rio Grande do Sul 60 (85.7) in urban areas 42 (60.0%). Clinical features the most frequent comorbidity was Hypertension 47 (67.1%), with a hospital stay of 12.5 days, three days in the intensive care unit, and surgery to change the heart valve More procedure performed 40 (57.1%). It was concluded that after analyzing the data, patients have a degree of anxiety and depression highest in the preoperative phase, with significant statistical decrease these symptoms follow up three months after the procedure (phase III). Regarding quality of life, it is concluded that cardiac surgery has a positive impact on the quality of life of patients in all domains evaluated, statistically significant, especially after 3 months of procedure